2019
DOI: 10.3390/su11082213
|View full text |Cite
|
Sign up to set email alerts
|

Exploring a Moderate Operation Scale in China’s Grain Production: A Perspective on the Costs of Machinery Services

Abstract: Due to the indivisibility of agricultural machinery in production, limited farm sizes have reduced mechanization efficiency and increased the cost of grain production in China. As a result, the development of a moderate-scale farming system has been proposed by academic communities and policy makers. However, it is still hotly debated how to determine a moderate farm scale. We offer a new perspective on the costs of machinery services. This manuscript employs the threshold model and uses the nationally represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
1
7
0
1
Order By: Relevance
“…The ultra-small-scale operation of cultivated land especially occurs in the grain production core area, the research in Henan province has shown that the average number of plots per household is 4.13, and the average area of each cultivated land is lower than 0.1 hectares [22]. Compared with the requirements of agricultural modernization, these small plots seriously impede the widespread application of large farm machinery [53], and the excessively scattered agricultural ultra-small-scale management has shown remarkable inadaptability in China. CLT is the most important means to promote appropriate management scales of cultivated land in China [54].…”
Section: Cultivated Land Management Scale and Cultivated Land Green U...mentioning
confidence: 99%
“…The ultra-small-scale operation of cultivated land especially occurs in the grain production core area, the research in Henan province has shown that the average number of plots per household is 4.13, and the average area of each cultivated land is lower than 0.1 hectares [22]. Compared with the requirements of agricultural modernization, these small plots seriously impede the widespread application of large farm machinery [53], and the excessively scattered agricultural ultra-small-scale management has shown remarkable inadaptability in China. CLT is the most important means to promote appropriate management scales of cultivated land in China [54].…”
Section: Cultivated Land Management Scale and Cultivated Land Green U...mentioning
confidence: 99%
“…地 理 科 学 进 展 第 39 卷 户耕地的资产价值。近年来山区坡耕地弃耕、 撂荒 和零租金流转等现象在全国范围内较为普遍 [11][12][13][14][15][16][17][18] 。 1992-2017 年, 全国范围内有耕地撂荒记录的县市 达到 165 个, 主要集中在湖北、 重庆、 甘肃、 云南、 四 川、 江西和安徽南部等地区 [11] ; 基于全国山区县的 抽样调查显示, 2014-2015 年, 78%的村庄出现了 耕地撂荒, 耕地撂荒率为 14.3% [11][12][13][14] 。与此同时, 山 区耕地零租金流转的比例已超过 70% [15,[17][18] [19][20] [3] [21] 。养老需求下限计算公式: [25] 。 华南农业大学 "土地适度规模经营" 课题组认为平 原地区户均最优面积为 88~117 亩 [24] ; 中国科学院的 研究发现, 若要降低农户机械成本, 最优的农场规 模最小应为 50 亩 [25] [27][28] Abstract: Under the background of a large population and scarce land resources and the dual structure of land property right, the cultivated land resources in China have been the lifeline of farmers, and their social security function is considered the stabilizer of society. But this view has been increasingly questioned in recent years.…”
unclassified
“…In the persistence of small-scale farming size in China, many innovations from technology advancements, pathways of knowledge transfer to farmers, and new management skills are less effective due to high fixed costs of adoption [11,59]. Thus, Xu et al [60] proposed that increasing the size of farms effectively improves per-worker soybean productivity in China. However, as shown in Table 6, a negative relationship between agricultural credit and soybean yields can be seen.…”
Section: Long-run Estimates and Causality Analysismentioning
confidence: 99%